Intermediate-Term Outcomes of Dual Adult versus Single-Kidney Transplantation: Evolution of a Surgical Technique. (10th July 2016) - Islam, Ana K.; Knight, Richard J.; Mayer, Wesley A.; Hollander, Adam B.; Patel, Samir; Teeter, Larry D.; Graviss, Edward A.; Saharia, Ashish; Podder, Hemangshu; Asham, Emad H.; Gaber, A. Osama
Abstract : Background . Acceptance of dual kidney transplantation (DKT) has proven difficult, due to surgical complexity and concerns regarding long-term outcomes. We herein present a standard technique for ipsilateral DKT and compare outcomes to single-kidney transplant (SKT) recipients. Methods . A retrospective single-center comparison of DKT and SKT performed between February 2007 and July 2013. Results . Of 516 deceased donor kidney transplants, 29 were DKT and 487 were SKT. Mean follow-up was 43 ± 67 months. DKT recipients were older and more likely than SKT recipients to receive an extended criteria graft (p < 0.001 ). For DKT versus SKT, the rates of delayed graft function (10.3 versus 9.2%) and acute rejection (20.7 versus 22.4%) were equivalent (p = ns). A higher than expected urologic complication rate in the DKT cohort (14 versus 2%, p < 0.01 ) was reduced through modification of the ureteral anastomosis. Graft survival was equivalent between DKT and SKT groups (p = ns) with actuarial 3-year DKT patient and graft survivals of 100% and 93%. At 3 years, the groups had similar renal function (p = ns). Conclusions . By utilizing extended criteria donor organs as DKT, the donor pool was enlarged while providing excellent patient and graft survival. The DKT urologic complication rate was reduced by modification of the ureteral anastomosis.